THE INFLUENCE OF ADDITIONAL INCOME ON EMPLOYEE PERFORMANCE - Yasin, Fatah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the impact of additional income on employee performance. The research focuses on how financial incentives influence motivation, productivity, and overall job satisfaction. Method: By utilizing qualitative and quantitative methods, the study examines employees' responses to supplementary earnings in various organizational settings. Results: The findings suggest that additional income positively influences employee performance, although non-monetary factors also play a crucial role. Novelty: This study highlights the combined effects of financial and non-monetary factors on employee performance, providing a comprehensive perspective on motivation and job satisfaction.